2012
DOI: 10.1111/j.1463-1318.2012.03005.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of survival based on resection margin status following surgery for recurrent rectal cancer

Abstract: Patients undergoing R0 resection have the greatest survival advantage following surgery for recurrent rectal cancer. There is a survival advantage for R1 over R2 resection, but there may be no benefit of R2 resection over palliative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
87
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 39 publications
6
87
0
2
Order By: Relevance
“…In our study the survival time of patients after R0 resection was longer in comparison to non-radical resection group. This finding is in agreement with the results of meta-analysis by Bhangu et al who found no survival benefit of macroscopically non-radical (R2) resection over non-resection (laparotomy) [21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study the survival time of patients after R0 resection was longer in comparison to non-radical resection group. This finding is in agreement with the results of meta-analysis by Bhangu et al who found no survival benefit of macroscopically non-radical (R2) resection over non-resection (laparotomy) [21].…”
Section: Discussionsupporting
confidence: 93%
“…Radical (R0) resection of LR is associated with at least twice higher survival than in non-radical (R1/R2) resection and remains the treatment of choice [21,22]. The tumor-free resection margin is a favorable prognostic factor for improved local control and overall survival [19][20][21][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 also, several studies have shown that complete surgical resections provide a significant survival advantage compared with incomplete resections. [11][12][13]15,17,19,21,[26][27][28][29][30][31][32] in the included studies, most recurrences were treated with chemoradiation instead of radiotherapy alone. in patients with PRC, chemoradiation results in better lC than radiotherapy alone, without a positive effect on os.…”
Section: Discussionmentioning
confidence: 99%
“…Hastaların sadece %20-30'unda R0 rezeksiyonlar başarılabilir. [6] Diğer taraftan %68 gibi yük-sek oranlara ulaşan ameliyat sonrası komplikasyon oranları bildirilmiştir. [7][8][9][10][11][12] Kemoterapi (KT) ve eksternal radyoterapi (EBRT) sadece palyatif fayda sağlamaktadır.…”
unclassified